(untitled) (European Journal of Language and Literature, 2017)
The present paper aims to evidence the literary translation as a cultural bridge between the two countries, Albania and Spain. It is a topic which has interests in terms of literary translation because the literary translation Albanian-Spanish and vice versa is a non-treated topic in our country. Literature is a bridge between the two countries and language possesses all the characteristics of culture, because when it is translated it is produced an exchange of linguistic systems. In this paper, we will present chronological data on the number of literary translations in both countries, respectively in Albania and Spain, and we will explain the importance of literary translation as a process that connects cultures, inasmuch as the literary translation aims to transfer literary or artistic experiences of a culture to another culture. Moreover, this paper will provide an overview of the impact of literary translation in both cultures, Albanian and Spanish.